Genomic analysis of progenitors in viral infection implicates glucocorticoids as suppressors of plasmacytoid dendritic cell generation - Yeara Jo; Trever T. Greene; Carolina Chiale; Kai Zhang; Ziyan Fang; Simone Dallari; Nuha Marooki; Wei Wang; Elina I. Zuniga (Proceedings of the National Academy of Sciences, 2025)
Plasmacytoid Dendritic cells (pDCs) are the most potent producers of interferons, which are critical antiviral cytokines. pDC development is, however, compromised following a viral infection, and this phenomenon, as well as its relationship to conventional (c)DC development is still incompletely understood. By using lymphocytic choriomeningitis virus (LCMV) infection in mice as a model system, we observed that DC progenitors skewed away from pDC and toward cDC development during in vivo viral infection. Subsequent characterization of the transcriptional and epigenetic landscape of fms-like tyrosine kinase 3 + (Flt3 + ) DC progenitors and follow-up studies revealed increased apoptosis and reduced proliferation in different individual DC-progenitors as well as a profound type I interferon (IFN-I)-dependent ablation of pre-pDCs, but not pre-DC precursors, after both acute and chronic LCMV infections. In addition, integrated genomic analysis identified altered activity of 34 transcription factors in Flt3 + DC progenitors from infected mice, including two regulators of Glucocorticoid (GC) responses. Subsequent studies demonstrated that addition of GCs to DC progenitors led to downregulated pDC-primed-genes while upregulating cDC-primed-genes, and that endogenous GCs selectively decreased pDC, but not cDC, numbers upon in vivo LCMV infection. These findings demonstrate a significant ablation of pre-pDCs in infected mice and identify GCs as suppressors of pDC generation from early progenitors. This provides a potential explanation for the impaired pDC development following viral infection and links pDC numbers to the hypothalamic–pituitary–adrenal axis.